ESTUDO COMPARATIVO DUPLO-CEGO DA EFICACIA E SEGURANCA DO CILAZAPRIL COMPARADAS A NIFEDIPINE 'RETARD' NO TRATAMENTO DA HIPERTENSAO ARTERIAL LEVE E MODERADA - Velasco-Cornejo, I. F. [UNESP] (1994)
Purpose: To evaluate the antihypertensive efficacy and safety of cilazapril compared to nifedipine retard in mild to moderate hypertension. Methods: Forty randomized out-patients with mild moderate hypertension, diastolic pressure (DP) between 95 and 115 mmg/Hg, with placebo for 15 days were randomized and allocated for treatment, double-blind, once daily with cilazapril 2.5 mg (n = 20) or nifedipine retard 20 mg (20 = n) for four weeks. The non-responders (DP > 90 mmHg) had the dosage increased twice, b.i.d., while responders were maintained up to 10 weeks. Clinical visits were performed before, at baseline and every two weeks and the laboratory test was performed after placebo run-in, 4th and 10th weeks of treatment. Results: The blood pressure (BP) were similar between groups at the end of the placebo (cilazapril 151 ± 14/103 ± 5 - nifedipine 157 ± 17/108 ± 7 mmHg, p > 0.05). DP decreased already at second weeks (cilazapril 95 ± 9 - nifedipine 96 ± 11 mmHg, p < 0.05, compared to week 0) in both groups at the end of study with no differences inter groups. BP normalization was obtained in 58% of the patients with cilazapril and in 61% in the nifedipine group. Adverse biochemical effects were not observed in any group. Six (16%) patients of the cilazapril and 15 (39%) of nifedipine related collateral events, although no difference were observed between groups. Conclusion: Cilazapril 2.5 to 5 mg normalized BP in 58% of mild and moderate hypertension patients, and this efficacy was similar to sustained-release nifedipine 20 to 40 mg. Cilazapril had no adverse effects on the biochemical parameters with low incidence of collateral effects.